Edukasi Literasi Keuangan Rumah Tangga, Program Pra Nikah dan Pemanfaatan Remunggai dalam Menurunkan Angka Stunting di Kecamatan Air Besi Kabupaten Bengkulu Utara - Safrianti, Sintia; Waliamin, Janusi; Puspita, Veny; Oktavallyan Saputri, Dwi; Alfanda, Wahyu; Abdul Aziz, Rozainun (Fakultas Pertanian, 2024)
Community service was carried out in Air Besi District, North Bengkulu, which aimed to address several important issues related to public health and welfare. This community service succeeded in achieving several main objectives, namely: (1) reducing the prevalence of stunting by increasing public knowledge about nutrition and healthy eating patterns, (2) increasing pre-marital knowledge with education on optimal pre-marital preparation, including health checks, proper nutritional intake, and a healthy lifestyle, to support maternal and infant health, (3) increasing public understanding of financial management to plan and manage finances more efficiently, which has the potential to reduce financial burdens and improve quality of life, and (4) increasing public knowledge about nutrition and the use of remunggai as an important source of nutrition in supporting health. This community service is expected to strengthen and continue the success of the program in improving public welfare and reducing the prevalence of stunting in Air Besi District, North Bengkulu.